Analysis Of Factors Affecting Sugarcane Farmers' Income (Case Study: PT. PG Rajawali II Unit PG. Sindanglaut) - Irfan Daud Hiban; Doni Nugraha; Dina Dwirayani (Cita Konsultindo Research Center, 2024)
This study aims to analyze the factors that influence the income of sugarcane farmers in PT. PG Rajawali II Unit PG Sindanglaut. The research examines three main factors: capital, land size, and labor, which are expected to have a significant impact on farmers' income. The study utilizes a descriptive quantitative approach and regression analysis to evaluate the data collected through surveys of 478 farmers in the Cirebon region. The findings will provide insights into how these factors correlate with income levels and help to inform future strategies for improving farmer livelihoods..